Bib Sign in Proximal Descending Thoracic Aorta Rupture on CT Angiography: Presentation of a Paradigmatic Case. (5th December 2022) - Pierro, Antonio; Posa, Alessandro; Iorio, Luca; Tanzilli, Alessandro; Cucciolillo, Lucia; Quinto, Fabio; Sciandra, Mariacarmela; Iezzi, Roberto; Cilla, Savino
Abstract : Thoracic aortic rupture may present with subtle clinical and CT-angiography findings. Recognition of the imaging features of early rupture is key for timely diagnosis and treatment. This report presents a new sign of incipient proximal thoracic aortic rupture on CT-angiography.